2020
DOI: 10.1021/acsaem.9b02466
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzing the Intercalation Storage Capacity of Aqueous Zinc-Ion Battery Constructed with Zn(II) Preinserted Organo-Vanadyl Hybrid Cathode

Abstract: This article reports the first instance of exploring a chemically Zn(II) preinserted organic−inorganic hybrid material [vanadyl ethylene glycolate or VEG, (VO(CH 2 O) 2 )] as an efficient cathode for rechargeable zinc-ion batteries (ZIBs). The control VEG electrode synthesized by a glycothermal process showed a modest specific capacity of 157 mAh/g at 0.1 A/g current density, however, suffered from poor rate capability and cycle stability due to structural dissolution. Chemically Zn(II) preinsertion into VEG (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…36,37,41 It has been shown that the localized Gaussian basis set (GTO) codes are more intuitively appropriate for solving the Hartree-Fock (HF) part of the Schrödinger equations implemented in the hybrid density functionals menthods. 37,41,[51][52][53][54] The periodic HSE06 DFT method has been implemented in the ab initio-based CRYSTAL17 suite program, 48 which effectively executes hybrid functional methods and facilitates standard application of the new methods to large-scale calculations of such materials with excellent performance, even with small-scale computing resources. The HSE06 method provides a more accurate electronic band gap compared to the other DFT methods.…”
Section: Methodology and Computational Detailsmentioning
confidence: 99%
“…36,37,41 It has been shown that the localized Gaussian basis set (GTO) codes are more intuitively appropriate for solving the Hartree-Fock (HF) part of the Schrödinger equations implemented in the hybrid density functionals menthods. 37,41,[51][52][53][54] The periodic HSE06 DFT method has been implemented in the ab initio-based CRYSTAL17 suite program, 48 which effectively executes hybrid functional methods and facilitates standard application of the new methods to large-scale calculations of such materials with excellent performance, even with small-scale computing resources. The HSE06 method provides a more accurate electronic band gap compared to the other DFT methods.…”
Section: Methodology and Computational Detailsmentioning
confidence: 99%
“…Pillaring of layer structured vanadium-and MnO 2 -based materials with metal ions, and structural water increase the interlayer spacing and favor the facile insertion/extraction of charge carrier. [71,112,[154][155][156][157][158][159][160][161]…”
Section: Pillar Effectmentioning
confidence: 99%
“…It has also been demonstrated recently that the pre-insertion of Zn 2 + ion into the organic-inorganic hybrid material and VOPO 4 • 2 H 2 O favors faster ionic diffusion and enhances the overall performance of the device. [159,160] The alkali metal ion pillared vanadium oxides have been extensively studied for LIBs, and it has also been extended to ZIBs. [166,167] Theoretical studies showed that the K + intercalated V 2 O 5 (K 0.5 V 2 O 5 ) has metallic behavior.…”
Section: Metal-ion Pillarsmentioning
confidence: 99%
“…3,4 This has triggered a significant research interest in improving the electrochemical performance of the electrodes and electrolytes of the existing LIBs to meet the immediate demand, as well as in exploring other rechargeable battery chemistries beyond Li-ion for applications where the battery cost and maintenance are rather more important factors than the energy density. 5–10…”
Section: Introductionmentioning
confidence: 99%